Development of a core outcome set for clinical trials in childhood asthma: a survey of clinicians, parents, and young people - Sinha Ian P (Trials, 2012)
Abstract Background In clinical trials in childhood asthma, outcomes reflecting short-term disease activity are frequently measured, whilst functional status, quality of life (QoL), and long-term treatment effects are rarely assessed. There is also non-uniformity across studies in the selection and measurement of outcomes within these domains. The development of a core outcome set has the potential to reduce heterogeneity between trials, lead to research that is more likely to have measured relevant outcomes, and enhance the value of evidence synthesis by reducing the risk of outcome reporting bias and ensuring that all trials contribute usable information. Methods Paediatricians and specialist nurses, identified through the British Paediatric Respiratory Society, completed a two-round Delphi survey. Separate cohorts of parents of children younger than 18 years, recruited in clinics, participated in each round. Young people with asthma, aged at least 13 years, participated in the first round. Outcomes were identified separately for preschool and school-aged children. We identified outcomes considered important in routine clinical assessment by clinicians and parents/young people. In round 1, 46 clinicians suggested outcomes they considered important when deciding whether to adjust a child’s asthma therapy regime, and 49 parents/young people were asked, using open questions, how they judged whether their child’s (for young people, their own) asthma therapy was appropriate. Two researchers independently classified responses into appropriate, corresponding outcomes. In round 2, 43 clinicians and 50 parents scored, from 0–4, the importance of each outcome suggested by at least 10 % of round 1 responders and selected the three most important. Results The most important outcomes, when making shared decisions about regular therapies for school-aged and preschool children with asthma, were daytime and nocturnal symptoms, exacerbations, QoL, and mortality. Results from parents and clinicians were generally concordant, but parents placed more emphasis on long-term treatment effects. Conclusions We have developed a methodology to identify outcomes of most relevance to clinicians, parents, and young people when evaluating regularly administered therapies for asthma. Daytime and nocturnal symptoms, exacerbations, QoL, and mortality are particularly important outcomes that should be measured and reported in all clinical trials of regular therapies for children with asthma.